Type 3 secretion system of Pseudomonas aeruginosa - Horna G. (2021)
Pseudomonas aeruginosa is an opportunistic pathogen, mainly affecting severe patients, such as those in intensive care units (ICUs). High levels of antibiotic resistance and a long battery of virulence factors characterise this pathogen. Among virulence factors, the T3SS (Type 3 Secretion Systems) are especially relevant, being one of the most important virulence factors in P. aeruginosa. T3SS are a complex “molecular syringe” able to inject different effectors in host cells, subverting cell machinery influencing immune responses, and increasing bacterial survival rates. While T3SS have been largely studied and the molecular structure and main effector functions have been established, a series of questions and further points remain to be clarified or established. The key role of T3SS in P. aeruginosa virulence has resulted in the search for T3SS-targeting molecules able to impair their functions and subsequently improve patient outcomes. This review aims to summarise the most relevant features of the P. aeruginosa T3SS. © 2021 Elsevier GmbH